Overcoming Theological Dilemmas: Fostering Religious Moderation through the Resolution of Faith and Rationality - Marjani, Gustiana Isya (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2023)
This study aims to explore pertinent philosophical approaches in order to analyze the primary dilemma associated with theological beliefs, which impede the efficacy of religious moderation within the Indonesian context. Consequently, the study endeavors to fortify the framework of religious moderation policies. By anchoring arguments and research within this philosophical paradigm, the author endeavors to establish a robust theoretical underpinning that substantiates the integration of faith and reason in the realm of religious moderation. The chosen methodology for this research comprises a comprehensive literature review, entailing the systematic gathering and analysis of diverse primary and secondary sources. Primary sources encompass relevant scholarly writings that directly address the subject of religious moderation, while secondary sources encompass a compendium of academic works, including books, journals, articles, and papers that specifically delve into the intricacies of this subject matter. The findings of this study demonstrate that the practice of religious moderation is frequently impeded by the exclusivity inherent in theological truths, which undermines the rationality of human actions. Therefore, a resolution between faith and reason is imperative to surmount this quandary, particularly through the facilitation and engagement in interfaith dialogues, the promotion of inclusive theological education, the cultivation of critical and rational thinking, the accentuation of universal moral values and religious virtues, the deepening of hermeneutics and moderation in interpretations, the distancing from identity politics, the spotlighting of spiritual experiences in religious praxis, and the emphasis on the fundamental right to freedom of religion.